Redescription of Orthopristis ruber and Orthopristis scapularis (Haemulidae: Perciformes), with a hybridization zone off the Atlantic coast of South America - Marceniuk, Alexandre Pires; Caires, Rodrigo Antunes; Machado, Leonardo; Cerqueira, Najila Nolie Catarine Dantas; de S. Serra, Rayla Roberta M.; Oliveira, Claudio (Zootaxa, 2019)
The genus Orthopristis includes seven valid species, three from the western Atlantic and five from eastern Pacific, while the available identification guides and taxonomic keys incorrectly recognize Orthopristis ruber as the only valid species found on the Atlantic coast of South America. Efforts to expand the inventory of fish species from the northern coast of Brazil led to the identification of two distinct species of Orthopristis from Atlantic South America, based on the analysis of coloration patterns and meristic data, as well as DNA. In the present study, the limits of Orthopristis ruber are reviewed, while Orthopristis scapularis is recognized as a valid species for the northern and northeastern coasts of South America. Based on intermediate morphological characteristics and nuclear DNA markers, a hybrid zone was identified off the state of Espírito Santo, on the eastern Brazilian coast. Additionally, considerations are made on the diversity and biogeography of the coastal marine and estuarine fishes found on the Brazilian coast.